Impacts of urban agriculture practices on food security in Klang Valley, Malaysia - Mah, Yuh Qing (2018)
Rapid urbanization and food price inflation had triggered the sense of food insecurity among the urban poor. Urban agriculture had been identified by the government as an alternative to improve food security. Therefore, the main objective of this study is to determine the most influenced factors that affect the willingness to participate in urban agriculture practices. A survey was conducted in Klang Valley where 100 respondents were interviewed through two stage cluster random sampling method. Collected data was analyzed using descriptive analysis and binary logistic regression analysis. The binary logistic regression analysis results indicated that gender and income groups are the significant factors in influencing the willingness to participate in urban agriculture practices. Male tends to have higher willingness to participate compared to female. The findings from the study also indicated that the category of lower income group has higher willingness to participate in urban agriculture practices. Besides, the study also revealed that urban agriculture practices do help in food bill reduction. Since urban agriculture is able to reduce monthly food bill thus it can be indicated to improve food security. Thus, the study suggests that urban agriculture should be promoted especially to the nation who is in the category of B20 where income group is low. Based on the findings of this study, some effort should be taken to promote the practice of urban agriculture in order to improve the food security issue. The government authority should trigger the awareness of food security issue among the nation in order to improve the willingness to participate in urban agriculture practices.